Combination of CRITIC Weighting Method and Multi-Attribute Utility Theory in Network Vendor Selection - Dwi Satria, M. Najib; Setiawansyah, Setiawansyah; Mesran, Mesran (Building of Informatics, Technology and Science (BITS), 2024)
The main problems in the selection of network vendors include uncertainty regarding the credibility and reliability of the vendor, which can result in the risk of product or service failure. Choosing a network vendor requires a thorough evaluation of the vendor's credibility and track record to ensure their reliability and experience in the industry. In addition, the technology compatibility and flexibility of the product need to be checked to ensure seamless integration with existing infrastructure and the ability to adapt to evolving needs. The combination of the CRITIC weighting and MAUT methods can result in a robust and holistic approach in the decision support system. CRITIC is used to determine the relative weight of each criterion based on the correlation analysis between the criteria, thus helping to reduce subjectivity and improve the objectivity of the assessment. Once the criterion weights are set using CRITIC, MAUT can be used to calculate the utility score of each alternative based on the weights of that criterion. MAUT allows the integration of decision-maker subjective preferences into the analysis, thus allowing for a more thorough and accurate evaluation of the alternatives being evaluated. The results of the network vendor ranking show that Nusanet gets the first rank with a final score of 0.6214, Zitline gets the second rank with a final score of 0.5317, MMS gets the third rank with a final score of 0.5276, TMS gets the fourth rank with a final score of 0.4147, and JPDN gets the fifth rank with a final score of 0.3677. This combination of the CRITIC and MAUT methods provides a comprehensive approach to network vendor selection, ensuring that decisions are based on structured, transparent, and measurable analysis, resulting in the most optimal vendor selection for the organization's needs.